Correction: Torularhodin, isolated from Sporidiobolus pararoseus, inhibits human prostate cancer LNCaP and PC-3 cell growth through Bcl-2/Bax mediated apoptosis and AR down-regulation. Issue 13 (26th January 2016) - Du, Chao; Li, Yingchao; Guo, Yahui; Han, Mei; Zhang, Weiguo; Qian, He
Abstract : Correction for 'Torularhodin, isolated from Sporidiobolus pararoseus, inhibits human prostate cancer LNCaP and PC-3 cell growth through Bcl-2/Bax mediated apoptosis and AR down-regulation' by Chao Du et al., RSC Adv., 2015, 5, 106387–106395.